Khay Wey receives Setegap Ventures Petroleum Industry Excellence Prize - Siti Nurfarmy, Ibrahim (2022)
KUANTAN, 17 March 2022 – A Diploma in Chemical Engineering (Process Plant) graduand, Ng Khay Wey, 23, did not expect to be selected as the Excellence Prize Setegap Ventures recipient Petroleum Sdn. Bhd. in the Universiti Malaysia Pahang (UMP) 15th Convocation Ceremony.